2020
DOI: 10.3390/ijerph17124428
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors for Bullying at 11 Years of Age in a Spanish Birth Cohort Study

Abstract: (1) Background: Bullying affects a large number of children worldwide. This study has two objectives, to provide data on the prevalence of bullying in Spain, and to identify risk and protective factors associated with bullying. (2) Methods: Participants were 858 eleven-year-old children. Bullying was assessed using a short version of the Olweus Bully Victim Questionnaire, and the following data were gathered to explore potential predictors: individual (inattention, behavior problems, attention deficit hyperact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 68 publications
(112 reference statements)
0
9
0
11
Order By: Relevance
“…Un estudio realizado durante el confinamiento de COVID 19 ha mostrado que los bajos niveles de depresión y de estrés postraumático están asociados al apoyo familiar, pero no al apoyo de otras personas significativas, como amigos o parejas (Lee et al, 2018). Compartir más tiempo con los cuidadores, dialogar con ellos para comprender y aliviar la ansiedad y el establecer patrones de vida equilibrados, como las horas de sueño, puede aumentar el sentimiento de cohesión, seguridad y apoyo familiar y social y fortalecer la resiliencia tanto en adolescentes victimizados como en los que no lo han sido (Babarro et al, 2020;Guessoum, 2020). Además, se ha demostrado que en situaciones donde se necesita la colaboración de todos, como en tiempos de guerra, se refuerza el sentimiento de utilidad y de pertenencia al grupo y disminuye el número de suicidios (Chu et al, 2017).…”
Section: Conclusiónunclassified
“…Un estudio realizado durante el confinamiento de COVID 19 ha mostrado que los bajos niveles de depresión y de estrés postraumático están asociados al apoyo familiar, pero no al apoyo de otras personas significativas, como amigos o parejas (Lee et al, 2018). Compartir más tiempo con los cuidadores, dialogar con ellos para comprender y aliviar la ansiedad y el establecer patrones de vida equilibrados, como las horas de sueño, puede aumentar el sentimiento de cohesión, seguridad y apoyo familiar y social y fortalecer la resiliencia tanto en adolescentes victimizados como en los que no lo han sido (Babarro et al, 2020;Guessoum, 2020). Además, se ha demostrado que en situaciones donde se necesita la colaboración de todos, como en tiempos de guerra, se refuerza el sentimiento de utilidad y de pertenencia al grupo y disminuye el número de suicidios (Chu et al, 2017).…”
Section: Conclusiónunclassified
“…Dalam survey yang dilakukn pada tahun 2009-2010 menunjukkan hasil bahwa di negara Eropa, Canada, dan USA didapatkan prevalensi kejadian bulying sekitar 2% smpai 32% dan sekitar 1% sampai 26% dalam kasus perbatan bullying (Babarro, 2020).…”
Section: Jlbunclassified
“…Hasil penelitian menunjukkan bahwa semakin tinggitingkat attenion deficit hyperactivity disorder symptomatolog meningkatkan risiko bullying,sedangkan sampel yang memiliki hubungn yang l baik dengan orang tua dan dukungan sosial yang kuat memiliki risiko terkena bulying yang lebih rendah. Kemudian untuk anak-anak yang memiliki hubngan teman sebaya yang kuat dan dukungan sosial yang tinggi juga meiliki resiko yang lebih rendah untuk terkena bullying (Babarro et al, 2020).…”
Section: Jlbunclassified
“…In fact, there are several risk and protective factors at the individual, family, school, and community level that are dynamically linked to the child's psychosocial response to experiences of victimization and being an aggressor. Some of the risk factors include presence of a neurodevelopmental disorder, low socioeconomic status, poor parental mental health, and family conflict [4]. Research has also identified several protective factors including prosociality, good academic grades, and a positive school climate [4].…”
mentioning
confidence: 99%
“…Some of the risk factors include presence of a neurodevelopmental disorder, low socioeconomic status, poor parental mental health, and family conflict [4]. Research has also identified several protective factors including prosociality, good academic grades, and a positive school climate [4]. Since school bullying has grave consequences for both victims and perpetrators [5], it is imperative that schools implement effective violence prevention programs that help in early identification and prevention of school bullying.…”
mentioning
confidence: 99%